2019
DOI: 10.3390/diseases7010020
|View full text |Cite
|
Sign up to set email alerts
|

Timely Interventions for Children with ADHD through Web-Based Monitoring Algorithms

Abstract: The aim of this study was to evaluate an automated trigger algorithm designed to detect potentially adverse events in children with Attention-Deficit/Hyperactivity Disorder (ADHD), who were monitored remotely between visits. We embedded a trigger algorithm derived from parent-reported ADHD rating scales within an electronic patient monitoring system. We categorized clinicians’ alert resolution outcomes and compared Vanderbilt ADHD rating scale scores between patients who did or did not have triggered alerts. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Telehealth has been recommended as an effective means to increase access and improve engagement for pediatric BH services[ 149 , 150 ]. In children with ADHD, meaningful changes in functioning have been captured through telehealth interventions[ 125 - 127 ], and several evidence-based psychosocial interventions for pediatric behavioral problem have been adapted for telehealth application[ 151 ].…”
Section: Discussionmentioning
confidence: 99%
“…Telehealth has been recommended as an effective means to increase access and improve engagement for pediatric BH services[ 149 , 150 ]. In children with ADHD, meaningful changes in functioning have been captured through telehealth interventions[ 125 - 127 ], and several evidence-based psychosocial interventions for pediatric behavioral problem have been adapted for telehealth application[ 151 ].…”
Section: Discussionmentioning
confidence: 99%
“…trivoxhealth.com), which enables clinicians to administer online ADHD clinical questionnaires and rating scales to parents and teachers to monitor patients remotely, between visits, and at customizable intervals. 58 This includes a notification for clinicians when new data are available to view and an alert notification if there is potentially actionable data. They found that the TriVox Health trigger algorithm facilitated timely changes in the care plan between face-to-face visits because nurses were able to successfully contact parents in response to the alerts.…”
Section: Stand-alone Software Systemsmentioning
confidence: 99%
“…Two-thirds of the alerts led to a care plan change before the next scheduled appointment. 58 Epstein et al 59 developed an ADHD Web portal (now available at www. mehealth.com) in an effort to integrate ADHD QI efforts and provide multiple clinically salient functionalities.…”
Section: Stand-alone Software Systemsmentioning
confidence: 99%
“…The study outcomes showed that the institution's EHR ADHD template was feasible in assessing and monitoring ADHD treatment outcomes by accurately classifying ADHD, capturing ADHD information, and promptly communicate findings between parents and teachers. In response to omitted and incomplete documentation of DSM-V criteria for ADHD, Lukomski et al (2022) embedded DSM-V criteria for ADHD into the EHR, which improved provider documentation by 50%.…”
Section: Introductionmentioning
confidence: 99%
“…The DSM-V has been determined to be more precise in diagnosing ADHD symptoms compared with the DSM-IV criteria (Epstein & Loren, 2013). Because the criteria have been revised, many providers may not be documenting the DSM-V criteria being met to support diagnosis, which can contribute to inaccurate diagnosis and fragmented ADHD management (Lukomski et al, 2022). The DSM-V has been shown to have high sensitivity (100%), specificity (71.1%), and predictive value (85.1%) in the diagnosis of ADHD (Ghanizadeh, 2013).…”
Section: Introductionmentioning
confidence: 99%